Faktor-Faktor yang Berhubungan dengan Kepemimpinan Kepala Ruangan Dalam Pengelolaan Krisis Covid-19 Di Rumah Sakit Kota Padang Tahun 2022 - Rani Permata Sari; Yulastri Arif; Lina Febrianti (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The occurrence of a crisis situation caused by COVID-19 forces the head of the room to adjust its leadership to the conditions of the preparation, implementation, and evaluation during the COVID-19 crisis situation so that it can run the survival of an inpatient room. This study aims to determine the "Factors Related Leadership Leadership With Indoor Leadership Management of COVID-19 Crisis In Padang City Hospital 2022". This type of the research is Crossectional study. The population in this study were all nurses at RSUD Dr. Rasidin Padang and RSI Ibnu Sina Padang. With the sample of 183 respondents. Sampling using purposive sampling technique. Data collection in this study used questionnaires with univariat and bivariat analysis. From the results of the study, it is known that the personal characteristics of the leader in the good category are 51.4%, the factor of led group in the poor category of 51.4% and the category situation factor is 51.4%. From the results of the Chi Square test were obtained by all p _ value <0.05, there is a relationship between personal characteristics of leader with crisis management stage, the relationship between led group by the stage of crisis management, and the relationship between situation factors and the management stage. With the conclusion that there is a relationship between each factor studied by indoor leadership in the management of the COVID-19 crisis situation. The expected advice for hospitals can provide communication training and caring behavior the spatial leadership to face of the crisis so that it can improve nurse performance in providing nursing care.Â